Giant Cell Myocarditis in a Patient With Crohn's Disease, Treated with Etanercept – A Tumour Necrosis Factor-Alpha Antagonist - C Nash; R Panaccione; LR Sutherland; JB Meddings (Canadian Journal of Gastroenterology)
Cardiac disease in association with inflammatory bowel disease (IBD) is uncommon. Reports include pericarditis, pericardial effusion, myocarditis, myocardial infarction, endocarditis and arrythmias. Myocardial inflammation related to IBD may be due to a drug hypersensitivity reaction or micronutrient deficiency, or may be secondary to the underlying IBD as an extraintestinal manifestation. In this setting, myocarditis usually presents as congestive heart failure and/or refractory arrhythmia. Prognosis varies among reported cases, including complete recovery, remission with recurrence and fatal disease. Treatment of myocarditis has included aminosalicylates and immunosuppressive medications. Recently, newer therapies for IBD have been developed, such as tumour necrosis factor-alpha (TNF- α) antagonists. The present report describes a case of a 46-year-old man with clinical and endoscopic evidence of moderately active colonic Crohn's disease who developed congestive heart failure due to giant cell myocarditis. Little clinical improvement occurred with immunosuppressive therapy. Only after the addition of etanercept, a TNF- α p75 receptor antagonist, did complete clinical resolution occur. These authors conclude that the use of TNF- α antagonists may be considered in the treatment of life-threatening extraintestinal manifestations of inflammatory bowel disease.